The Influence of Talent Management on Employee Retention through Employee Engagement with Organizational Culture as a Moderation Variable: A Study on the Banking Sector in Makassar City - Andi Wirandani Natsir; Muh Rais; Sukmawati Sukmawati; Dewi Natalia (Economics and Digital Business Review, 2026)
This study examines the influence of talent management on employee retention, combining employee engagement as a mediating variable and organizational culture as a moderation factor in the banking sector in Makassar, Indonesia. Based on the Resource-Based View (RBV) and Social Exchange Theory (SET), this study aims to provide a comprehensive understanding of how strategic human resource practices affect employee retention through psychological and contextual mechanisms. A quantitative research design was used, with data collected from 250 banking employees using a structured questionnaire. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess measurement and structural models, including the effects of mediation and moderation. These findings reveal that talent management has a significant positive effect on employee engagement and employee retention. Employee engagement also significantly affects employee retention and partially mediates the relationship between management and talent retention. In addition, organizational culture significantly moderates the relationship between talent management and employee engagement, as well as between employee engagement and employee retention, reinforcing this effect under supportive cultural conditions. The study contributes to the literature by integrating RBV and SET in a single framework and simultaneously testing the effects of mediation and moderation, which remained limited in previous studies. The results highlight the importance of aligning talent management practices with organizational culture to improve employee engagement and retention. In practical terms, the findings provide strategic insights for banking institutions to develop integrated human resources policies that drive sustainable employee retention in a competitive labor market. Keywords: Talent Management, Employee Engagement, Employee Retention, Organizational Culture, PLS-SEM, Banking Sector